A good woman - Steel, Danielle (Delacorte Press, 2008)
Nineteen-year-old Annabelle Worthington was born into a life of privilege, raised amid the glamour of New York society, with glorious homes on Fifth Avenue and in Newport, Rhode Island. But everything changed on a cold April day in 1912, when the sinking of the Titanic shattered her family and her privileged world forever. When she is betrayed, and pursued by a scandal she does not deserve, Annabelle flees New York for war-ravaged France, hoping to lose herself in a life of service. There, in the heart of the First World War, in a groundbreaking field hospital run by women she finds her true calling. And when the war ends, Annabelle begins a new life in Paris--now a doctor, a mother, her past almost forgotten...until a fateful meeting opens her heart to the world she had left behind and she returns to New York one more time.